#TITLE_ALTERNATIVE# - KHARISMA PUTRA (NIM 15107032); Pembimbing: Dr. Albertus Deliar, S.T,M.T dan Riantini Virtriana, EGI
Along with the times, the needs of people in improving the quality of life including land increasing from time to time in line with population growth and accompanying social events. Such improvements led to changes in land use over time. West Java as one of the largest province in Indonesia with population growth and increasing economic activity has undergone considerable land use over time. To find these changes required a technology that provides information on land in West Java. Information about changes in LULC can be obtained from various sources, one of which is a satellite image. By comparing satellite images on 2 period in the same area, it brings changes to LULC in the region. However, a comparison of this image is sometimes shows some of the changes are not likely to occur, such as the building turned into a forest. To learn more about the changes in the actual case, required an analysis of the changes. One technology that can provide a source of information changes in an area of land is a satellite image of the same area from different years. However, a comparison of image data is often a problem among these changes likely occurred such as building change into forest. One method of analysis that can be used to analyze spatial data are based on analysis of Geographic Information Systems (GIS). GIS has the ability to perform analysis using spatial data. In addition, SIG able to conduct an analysis of some data, one of which is a comparison of two pieces of data LULC. In the present study, the analysis will be performed on the data of land use in West Java in 2005 and 2010 were derived from Landsat satellite imagery. The analysis process includes LULC data processing, data verification using Google Earth software, data analysis and statistical test data and drawing conclusions. Final Results of the study was the LULC change index in West Java from 2005 to 2010.